Morphological, Physiological, and Molecular Responses of Sweetly Fragrant Luculia gratissima During the Floral Transition Stage Induced by Short-Day Photoperiod - Liu, Xiongfang; Wan, Youming; An, Jing; Zhang, Xiujiao; Cao, Yurong; Li, Zhenghong; Liu, Xiuxian; Ma, Hong (Frontiers in Plant Science, 2021)
Photoperiod-regulated floral transition is vital to the flowering plant. Luculia gratissima ‘Xiangfei’ is a flowering ornamental plant with high development potential economically and is a short-day woody perennial. However, the genetic regulation of short-day-induced floral transition in L. gratissima is unclear. To systematically research the responses of L. gratissima during this process, dynamic changes in morphology, physiology, and transcript levels were observed and identified in different developmental stages of long-day and short-day-treated L. gratissima plants. We found that floral transition in L. gratissima occurred 10 d after short-day induction, but flower bud differentiation did not occur at any stage under long-day conditions. A total of 1,226 differentially expressed genes were identified, of which 146 genes were associated with flowering pathways of sugar, phytohormones, photoperiod, ambient temperature, and aging signals, as well as floral integrator and meristem identity genes. The trehalose-6-phosphate signal positively modulated floral transition by interacting with SPL4 in the aging pathway. Endogenous gibberellin, abscisic acid, cytokinin, and jasmonic acid promoted floral transition, whereas strigolactone inhibited it. In the photoperiod pathway, FD, COL12, and NF-Ys positively controlled floral transition, whereas PRR7, FKF1, and LUX negatively regulated it. SPL4 and pEARLI1 positively affected floral transition. SOC1 and AGL24 integrated multiple flowering signals to modulate the expression of FUL/AGL8, AP1, LFY, SEPs, SVP, and TFL1, thereby regulating floral transition. Finally, we propose a regulatory network model for short-day-induced floral transition in L. gratissima. This study improves our understanding of flowering time regulation in L. gratissima and provides knowledge for its production and commercialization.